2023
DOI: 10.1002/ps.7370
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis indicates the involvement of herbicide‐responsive and plant–pathogen interaction pathways in the development of resistance to ACCase inhibitors in Apera spica‐venti

Abstract: Background: The continuous use of the herbicides contributes to the emergence of the resistant populations of numerous weed species that are tolerant to multiple herbicides with different modes of action (multiple resistance) which is provided by nontarget-site resistance mechanisms. In this study, we addressed the question of rapid acquisition of herbicide resistance to pinoxaden (acetyl CoA carboxylase inhibitor) in Apera spica-venti, which endangers winter cereal crops and has high adaptation capabilities t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 70 publications
(150 reference statements)
0
7
0
Order By: Relevance
“…The DEGs identified in these processes in high numbers were GST and peroxidase . The up-regulated expression of GST has been observed in the lignin biosynthetic process and the detoxification of xenobiotic compounds in a herbicide resistance study …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DEGs identified in these processes in high numbers were GST and peroxidase . The up-regulated expression of GST has been observed in the lignin biosynthetic process and the detoxification of xenobiotic compounds in a herbicide resistance study …”
Section: Discussionmentioning
confidence: 99%
“…The upregulated expression of GST has been observed in the lignin biosynthetic process 57 and the detoxification of xenobiotic compounds in a herbicide resistance study. 58 Glutathione, a small thiol molecule, is a strong nonenzymatic antioxidant, which regulates multiple metabolic functions in plants and serves as a substrate for GST and glutathione peroxidase. 59 The GSH plays a key role in ROS detoxification in plants' stress response.…”
Section: Discussionmentioning
confidence: 99%
“…In this research, the P450s, GSTs, GTs, and ABC transporter genes that exhibited at least a 2-fold statistically significant change in at least one out of the four comparisons between treatments (R_C vs S_C, R_C vs R_T, S_T vs S_C, and R_T vs S_T) were validated (Wrzesińska-Krupa et al, 2023). The list of primers used for qRT-PCR is shown in supplementary table 1.…”
Section: Rna-seq Transcriptome and Qrt-pcr Validation Of The Selected...mentioning
confidence: 99%
“…These examples demonstrate the broad utility of UGT family enzymes for medicinal and agricultural applications. Therefore, researchers have put a huge effort into studying the protein superfamily of glycosyltransferases and exploring the use of these enzymes [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, only a tiny fraction of these UGT homologs have been characterized. In some studies, the substrates of UDP glycosyltransferase (UGT) homologs were not identified, but genetic experiments showed that they provided benefits to the plants, such as improved tolerance to drought [ 23 , 34 ], herbicides [ 27 , 28 , 35 ], and infection [ 36 , 37 ]. A vast number of UGT homologs are waiting to be explored for applications in many fields.…”
Section: Introductionmentioning
confidence: 99%